Identification of Putative Molecules for Adiponectin and Adiponectin Receptor and Their Roles in Learning and Memory in Lymnaea stagnalis - Kanta Fujimoto; Yuki Totani; Junko Nakai; Nozomi Chikamoto; Kengo Namiki; Dai Hatakeyama; Etsuro Ito (Biology, 2023)
Adiponectin enhances insulin sensitivity, which improves cognition in mammals. How adiponectin affects the mechanism’s underlying cognition, however, remains unknown. We hypothesized that experiments using the pond snail Lymnaea stagnalis, which has long been used in learning and memory studies and in which the function of insulin-like peptides affect learning and memory, could clarify the basic mechanisms by which adiponectin affects cognition. We first identified putative molecules of adiponectin and its receptor in Lymnaea. We then examined their distribution in the central nervous system and changes in their expression levels when hemolymph glucose concentrations were intentionally decreased by food deprivation. We also applied an operant conditioning protocol of escape behavior to Lymnaea and examined how the expression levels of adiponectin and its receptor changed after the conditioned behavior was established. The results demonstrate that adiponectin and adiponectin’s receptor expression levels were increased in association with a reduced concentration of hemolymph glucose and that expression levels of both adiponectin and insulin-like peptide receptors were increased after the conditioning behavior was established. Thus, the involvement of the adiponectin-signaling cascade in learning and memory in Lymnaea was suggested to occur via changes in the glucose concentrations and the activation of insulin.